2006
DOI: 10.1063/1.2410222
|View full text |Cite|
|
Sign up to set email alerts
|

Interlayer coupling in ferromagnetic epitaxial Fe3Si∕FeSi2 superlattices

Abstract: Ferromagnetic epitaxial B2-type Fe3Si∕FeSi2 superlattices were prepared on Si(111) at room temperature by facing target direct-current sputtering. The bilinear and biquadratic coupling constants J1 and J2 of the antiferromagnetically coupled superlattice were comparable to those of the similar superlattices using Fe layers although the saturation magnetization of Fe3Si is approximately half as large as that of Fe. The authors believe that this is due to the formation of a well-ordered quantum well in the space… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
34
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 7 publications
8
34
0
Order By: Relevance
“…This combination has the following specifics: (i) since the electrical conductivity of FeSi 2 spacer layers is an order of magnitude smaller than that of Fe 3 Si layers, a magnetoresistance effect in current-perpendicular-to-plane (CPP) geometry is expected to be detectable; (ii) the epitaxial growth of Fe 3 Si layers on Si(111) substrates is successively kept up to the top Fe 3 Si layer across FeSi 2 spacer layers, which is beneficial to the coherent transportation of spin-polarized electrons; (iii) a strong antiferromagnetic (AF) interlayer coupling can be induced among the ferromagnetic Fe 3 Si layers in spite of the saturation magnetization of Fe 3 Si being one-half of that of Fe; (iv) Fe 3 Si is feasible for a practical use since it has a high Curie temperature of 840 K; (v) d-electrons contribute to the electrical conduction in both layers. Thus far, we have confirmed that B2-type Fe 3 Si layers are epitaxially grown not only on a Si(111) substrate but also up to the top layer across NCFeSi 2 layers and ferromagnetic (F)/AF interlayer couplings are induced by controlling the thickness of NC-FeSi 2 layers [29][30][31][32][33].…”
Section: Introductionsupporting
confidence: 71%
See 2 more Smart Citations
“…This combination has the following specifics: (i) since the electrical conductivity of FeSi 2 spacer layers is an order of magnitude smaller than that of Fe 3 Si layers, a magnetoresistance effect in current-perpendicular-to-plane (CPP) geometry is expected to be detectable; (ii) the epitaxial growth of Fe 3 Si layers on Si(111) substrates is successively kept up to the top Fe 3 Si layer across FeSi 2 spacer layers, which is beneficial to the coherent transportation of spin-polarized electrons; (iii) a strong antiferromagnetic (AF) interlayer coupling can be induced among the ferromagnetic Fe 3 Si layers in spite of the saturation magnetization of Fe 3 Si being one-half of that of Fe; (iv) Fe 3 Si is feasible for a practical use since it has a high Curie temperature of 840 K; (v) d-electrons contribute to the electrical conduction in both layers. Thus far, we have confirmed that B2-type Fe 3 Si layers are epitaxially grown not only on a Si(111) substrate but also up to the top layer across NCFeSi 2 layers and ferromagnetic (F)/AF interlayer couplings are induced by controlling the thickness of NC-FeSi 2 layers [29][30][31][32][33].…”
Section: Introductionsupporting
confidence: 71%
“…External magnetic fields were applied in in-plane directions. In our previous study, we have confirmed that the interlayer coupling is alternatively changed with the FeSi 2 thickness from the change in the shape of magnetization curve [29]. Figure 4 implies that the Fe 3 Si layers are AF-coupled at a zero magnetic field and the minimum field for saturation of magnetization is approximately 5 kOe.…”
Section: Introductionsupporting
confidence: 69%
See 1 more Smart Citation
“…We have studied spintronics based on a Fe-Si system comprising ferromagnetic Fe3Si and semiconducting FeSi2 thus far [15,16,17,18,19,20,21,22,23,24,25,26]. The combination of Fe3Si and FeSi2 has the following merits [15,16,17,27,28]: (i) the spin injection efficiency might be higher than that in TMR junctions, because the mismatch of the electrical conductivities is less than an order of magnitude, and d electrons contribute to electrical conduction in both layers, (ii) Fe3Si can be epitaxially grown on Si(111) substrates even at room substrate temperature, which is beneficial to the coherent transportation of spin-polarized electrons, and (iii) Fe3Si is feasible for a practical use since it has a high Curie temperature of 840 K and a large saturation magnetization which is half of that of Fe. Additionally, FeSi2 has a large optical absorption coefficient, which is two orders of magnitude larger than that of Si at 1.2 eV.…”
Section: Introductionmentioning
confidence: 99%
“…We have studied Fe-Si based artificial lattices and spin valves comprising ferromagnetic Fe3Si and semiconducting FeSi2, prepared by sputtering, thus far [25][26][27][28][29][30][31][32][33][34][35][36]. Based on the preparation techniques in our previous researches, spin valve junctions comprising ferromagnetic Fe3Si and Fe layers and B-doped UNCD/a-C:H interlayers were prepared, and they were structurally investigated by transmission electron microscopy (TEM).…”
Section: Introductionmentioning
confidence: 99%